Environmental Education as a Catalyst to Teach Students About Their Economy and Politics - Shabalala, Nonkanyiso Pamella (Jurnal Pendidikan Indonesia Gemilang, 2023)
This conceptual paper highlights the potential of environmental education to teach students about their economy and politics. It begins by emphasising the significance of environmental education in shaping students' attitudes and behaviours towards environmental issues. The paper explores the link between the environment, economy, and politics and argues that comprehending these connections is essential for students to become informed and engaged citizens. Environmental education can offer a platform for teaching students about the intricacies of the economy and politics, including sustainability, resource allocation, and social justice. The paper draws upon examples from existing environmental education programs and presents strategies for integrating economic and political topics into environmental education curricula. Overall, the paper contends that environmental education can empower students to become informed and active participants in their economy and political systems, contributing to a more sustainable and equitable future.